Human Relations Dan Pemberian Kompensasi Sebagai Strategi Meningkatkan Motivasi Kerja Serta Dampaknya Terhadap Loyalitas Karyawan (Studi Pada Pt. National Sago Prima Kabupaten Kepulauan Meranti, Riau) - Cahyani, Indah; Kasmirudin, Kasmirudin (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the influence of human relations and compensation provision as strategies to enhance work motivation and their impact on employee loyalty (a case study at PT National Sago Prima, Kepulauan Meranti Regency, Riau). The research method employed is quantitative, with data collected through questionnaires distributed to all employees of the company selected using saturated sampling techniques. A total of 80 respondents participated, and the data were analyzed using the Partial Least Square (PLS) method with SmartPLS 4. The findings of this study indicate that the Human Relations variable, mediated by work motivation, has a positive and significant effect on employee loyalty, with a T-statistics value of 2.309 (> 1.96) and a P-value of 0.021 (< 0.05). Conversely, the Compensation variable, mediated by work motivation, shows a negative and insignificant effect on employee loyalty, with a T-statistics value of 1.244 (< 1.96) and a P-value of 0.214 (> 0.05). Based on these results, the mediating role of motivation between exogenous and endogenous variables can be not positive and not significant. Good interpersonal relations (human relations) create a conducive work environment, enhance motivation, and ultimately foster stronger employee loyalty. The combination of these factors makes a substantial contribution to both employee loyalty and overall organizational performance. Therefore, companies are encouraged to continuously improve the quality of workplace relationships and compensation systems in order to promote greater work motivation and optimal performance.